Characterisation of exogenous bacterial biofilm and its application in the decolourisation of textile wastewater - Mohd. Zahari, Maihafizah (2008)
Characterization of the bacterial biofilm and their applications in the bioremediation of textile wastewater, especially in colour removal activities, are the main interests in this study. A total of 18 bacterial strains were isolated from biofilm formed on support matrices collected in textile treatment pond. Of these, three isolates were capable of removing colour at more than 70% d-1 from filter sterilised textile wastewater (FSTW). These three isolates were further identified as Enterobacter aerogenes, Citrobacter freundii and Escherichia coli using 16S rRNA gene sequence analysis. These bacterial strains were further screened for copper (Cu2+) and chromium (Cr3+) tolerance. Results showed that Enterobacter aerogenes was resistant to both copper (2.15 mM) and chromium (0.5 mM) while Citrobacter freundii was only resistant towards copper (2.15 mM). Escherichia coli, however was sensitive to both metals. Evidence of biofilm formation during decolourisation was observed using Scanning Electron Microscopy (SEM). Semi-quantitative analysis for Cu2+ and Cr3+ accumulation in the biofilm was determined using Energy Dispersive X-ray (EDX) technique. Shake flasks study on colour removal was carried out using pure and mixed culture grown as biofilm on colourless polyurethane cubes (125 mm3) at 37ºC, 100 rpm. Mixed culture consisted of E. aerogenes, C. freundii and E. coli was used in a ratio of 1:1:1 (v/v). For both pure and mixed of culture biofilm, decolourisation of FSTW was optimum at 37ºC, pH 7 to 8, 10-12% (v/v) inoculum, agitated at 100 rpm under facultative anaerobic condition. The best C/N ratio for maximum rate of decolourisation was 5.3 for E. coli and 3.5 for C. freundii, E. aerogenes and mixed culture. Mixed culture biofilm was found to be the best decolouriser as indicated by the highest rate of decolourisation (9.04% h-1) in comparison with those of pure cultures (3.98-5.20 %h-1). Results also showed that decolourisation was not necessarily affected by specific growth rate (µ) or Yield (Y X/S) during colour removal. Mixed culture biofilm was applied for textile wastewater treatment. As a result, improvement of water quality was observed when compared to the Department of Environment (DOE) standard effluent limit (Environmental Quality Act, 1974). The results were as follows: BOD, 62.1 mg/L; COD, 99.4 mg/L; TSS, 65 mg/L, nutrient (nitrate 0.33 mg/L and phosphate 1.48 mg/L) and colour; 7.3 ADMI units, after 48 h incubation. Acclimatization of the mixed bacterial culture in the real wastewater is beneficial as it would increase the efficiency to improve wastewater quality except for sulphate removal.